Clinical Statistics for Odontogenic Disease in Patients Referred for Unknown Causes - Kamiyama, Hirona; Makiyama, Yasuhide; Masuda, Manabu; Shimosaka, Michiharu; Sakaki, Mika; Nishimura, Hitoshi; Wake, Hiroyuki; Okubo, Masakazu; Uchida, Takashi; Iida, Takashi; Nishimori, Hideta; Komiyama, Osamu; et al. (Japanese Journal of Orofacial Pain, 2019)
Abstract: To examine the characteristics of cases of patients referred to the Nihon University School of Dentistry at Matsudo Hospital for unknown causes who were ultimately diagnosed with odontogenic disease as the underlying disease, particularly among those clinically diagnosed with pulpitis. Methods: The study subjects were patients referred to us for unknown causes during the three-year period between January 2016 and December 2018（“patients of unknown causes”）. Results: Of 13,152 patients who visited us during the study period, 2,147 were referred from another hospital. Of these 2,147 patients, 287 were patients of unknown causes. The chief complaint in 76.3％ of these patients of unknown causes was orofacial pain. The percentage of women among the patients of unknown causes was significantly greater than that among the overall patients and referral patients. No characteristic age distribution was identified. Odontogenic disease was diagnosed as the underlying disease in 107 cases of the patients of unknown causes, of whom 32 cases had pulpitis, the most common disease. Diagnoses that had been made instead of pulpitis included the following: 7 cases of caries under inlay（5 cases） or in prosthesis（2 cases）; 6 cases of pulpitis after treatment for deep caries; and 5 cases of tooth crown crack or fracture. In addition, a diagnosis of non-odontogenic disease was made for 131 cases; the most common disease was TMD in 29 cases, followed by BMS in 25 cases and neuropathic pain in 10 cases. Conclusions: Odontogenic disease was diagnosed in 40％ or more of the patients referred for unknown causes. If orofacial pain is caused by odontogenic disease, the pain tends to be readily treatable. These results demonstrate the significance of correctly differentiating odontogenic disease from non-odontogenic disease when diagnosing the cause of orofacial pain.